Kebijakan Penal Mengenai Kriminalisasi Di Bidang Keuangan - Salman Luthan (Fakultas Hukum Universitas Islam Indonesia, 2009)
Research of penal policy on criminalization in financial affairs discusses two main problems: regulating policy on criminal offences, and regulating policy on criminal sanction for financial offences. The regulating policy on criminal offences shows an increase of various conducts that have been criminalized by legislator as a consequence of social change, economic and trade globalization, as well as technological development. Justification of criminalization base on liberal individualiatic theory and political affairs (ordening strafrect theory). The regulating policy on criminal sanction tends to strengthen criminal sanction of offences in financial affairs as a response to the weakness of law enforcement, as an effort to reform financial institutions, as a implementation of penal philoshophy of deterrence, and as a high “spirit” of legislators to punish the offenders.Key Words: penal policy, criminalization, finance